Tindak Pidana Penganiayaan Sebagaimana Diatur dan Diancam Pidana Dalam Pasal 351 ayat 1 KUHP (Studi Putusan PN Medan Nomor 1621/Pid.B/2023/PN Mdn - Laurenty Simanjuntak; Richie Nicodemus Munthe; Angelina Putri Gwen Sihotang; Parlaungan Gabriel Siahaan; Dewi Pika Lumban Batu (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
One of the most common crimes in society is child abuse. Article 351 paragraph (1) of the Penal Code (KUHP) regulates and threatens criminal offenses in Indonesian criminal law. Medan District Court Decision No. 1621/Pid.B/2023/PN Mdn, regarding criminal abuses, will be discussed in this article. This study analyzes events and court decisions. Research methods include analysis of court decisions and legal analysis of criminal behavior. Research results show that, according to the provisions of the Penal Code, abuse crimes can be classified into many types, including general abuse, mild abuse, intentional abuse and severe abuse. Important. Preventive and repressive measures are necessary to combat criminal acts. Criminal law is used to solve problems in society, while non-criminal methods focus on prevention. To bring justice to victims and all parties involved, law enforcement must understand the behavioral factors associated with criminal abuse.